A 90-day OECD TG 413 rat inhalation study with systems toxicology endpoints demonstrates reduced exposure effects of the aerosol from the carbon heated tobacco product version 1.2 (CHTP1.2) compared with cigarette smoke. II. Systems toxicology assessment. (May 2018) - Titz, Bjoern; Kogel, Ulrike; Martin, Florian; Schlage, Walter K.; Xiang, Yang; Nury, Catherine; Dijon, Sophie; Baumer, Karine; Peric, Dariusz; Bornand, David; Dulize, Remi; Phillips, Blaine; et al.
Abstract: Modified risk tobacco products (MRTPs) have the potential to reduce smoking-related health risks. The Carbon Heated Tobacco Product 1.2 (CHTP1.2) is a potential MRTP that uses a pressed carbon heat source to generate an aerosol by heating tobacco. Here, we report the results from the systems toxicology arm of a 90-day rat inhalation study (OECD test guideline 413) to assess the effects of CHTP1.2 aerosol compared with cigarette smoke (CS). Transcriptomics, proteomics, and lipidomics analyses complemented the standard endpoints. In the respiratory nasal epithelium, CS induced an adaptive tissue and inflammatory response, which was much weaker after CHTP1.2 aerosol exposure, mostly limited to the highest CHTP1.2 concentration (at twice the 3R4F CS concentration: 50 vs. 23 μg nicotine/L), in female rats. In the lungs, the effects of CS exposure included inflammatory and cellular stress responses, which were absent or much lower after CHTP1.2 aerosol exposure. Outside of the respiratory tract, CS and CHTP1.2 aerosol induced effects that were previously associated with exposure to any nicotine-containing aerosol, e.g., lower lipid concentrations in serum. Overall, this systems toxicology analysis complements and confirms the results from classical toxicological endpoints and further suggests potentially reduced respiratory health risks of CHTP1.2. Highlights: Systems toxicology assessment of potential modified risk tobacco product (CHTP1.2). Systems toxicology analyses were used to compare CHTP1.2 aerosol with smoke from the 3R4F reference cigarette. Assessment of exposure effects using proteomics, transcriptomics, and lipidomics. Reduced respiratory effects of CHTP1.2 aerosol compared with smoke from the 3R4F reference cigarette. Molecular analyses complemented apical endpoints, e.g. for inflammation and cell stress.